Ethnophysics Behind the Game of Egrang: Systematic Literature Review - Fitria Rahmawati; Wirawan Fadly; Utama Alan Deta (Universitas Lambung Mangkurat, 2026)
Local wisdom in Indonesia is a valuable cultural heritage. To preserve it, it can be introduced through school education, one of which is in physics education. Several researchers have studied local wisdom-based physics education in traditional games in depth, but no specific focus on the Egrang game has been found. Therefore, this study aims to analyze and identify the physics concepts found in the traditional game of stilts as an effort to integrate local wisdom into physics education. The research method used is a Systematic Literature Review (SLR) using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) design. Data was obtained from the Google Scholar database using the keyword “traditional Egrang game.” From the 1,270 documents identified, after screening based on inclusion and exclusion criteria, 7 articles were obtained that were suitable for analysis. The data was then analyzed descriptively to identify and classify physics concepts in the traditional Egrang game. The results of this study indicate that stilts are related to the physics concepts of work and energy, namely, mechanical energy consisting of kinetic and potential energy. Identification from the literature review also found other concepts such as rigid body equilibrium, balance, weight, and gravitational force. The results of this study confirm that stilts can strengthen students' understanding of physics concepts and the development of teaching materials in physics learning.